Developing Pre-Service Arabic Teachers’ Competence in Implementing Kurikulum Merdeka through Curriculum Development Course - Umi Hanifah; Syafi’i; Binti Adam, Zalika (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2024)
This study aimed to describe the preparations that pre-service Arabic teachers underwent to improve their ability to implement Kurikulum Merdeka through the Arabic Curriculum Development course. The study employed a qualitative descriptive method. Data were collected through observations, interviews, questionnaires, and documentation and were analyzed with Miles, Huberman, and Saldana’s interactive model of qualitative data analysis. The results show that the Arabic Curriculum Development course at the Faculty of Education and Teacher Training of Sunan Ampel Islamic State University was structured as follows: Presentation about Kurikulum Merdeka; introduction to the regulatory aspect of the curriculum; P5 and P2RA Modul writing assignment; discussions on the planning, learning, and assessment stages of Kurikulum Merdeka; review of Kurikulum Merdeka Learning Module model; and assignment to write Kurikulum Merdeka Learning Module. Through this course, the competence of the participants was prepared to implement the Kurikulum Merdeka in their School Field Practice (PLP).